How Protected are Teachers and School Personnel?: Critical Analysis of The Teacher Protection Act (Senate Bill 956) - Simbre, Abegail P.; Palad, Ingrid A.; Salazar, Catherine A. (International Journal of Social Learning (IJSL), 2021)
The contents of the Senate Bill 956, better known as the Teachers' Protection Policy Act was examined and analyzed based on the following themes, namely, support mechanisms for public school teachers and personnel, enhanced protection of public-school teachers and personnel, and training on guidelines and classroom discipline for public school teachers and personnel. According to the Republic Act, 4670 or the Magna Carta for Public School Teachers, the appropriateness of the act was checked to see how much help this bill can provide to the public-school teachers in the Philippines in terms of classroom discipline and classroom management. The bill poses excellent benefits to the public-school teachers. However, the Department of Education must identify which disciplinary acts or strategies are not categorized as child abuse and that there should be centralized policy implementations, seminars, and training to avoid misinterpretations and discipline avoidance among teachers. This paper hopes to contribute to a research-based, logical, and relevant drafting of HR policies and programs to support and protect the teachers as mandated in the Magna Carta for Public School teachers and SB 956. This study employed a qualitative method using resources available online.